Design and Simulation of an Antenna-Coupled Microbolometer at 30 THz - Angel Colin; Eduardo Pérez-Tijerina; Francisco Solis-Pomar (International Journal of Antennas and Propagation)
We propose a model of antenna-coupled microbolometer to be included in an array for receiving and detecting long wave infrared (LWIR) electromagnetic radiation. The antenna is joined to microstrip bandpass filters thus forming a single metal structure to define the operation frequency band. The antenna and microstrip filters are modeled in aluminum thin film. The microbolometer is modeled with superconducting niobium, all together on a silicon nitride membrane. The squared pixel structure is designed on a support frame of 20 μm in size. Simulation results for this antenna exhibit a frequency range of operation from 27 to 35 THz and is configured for two arrays, one of 10×10 and the other one of 50×50 elements. The device has been simulated by means of the commercial electromagnetic software (HFSS), which is based on the finite elements method. The predicted values for the figures of merit of this microbolometer are as follows: τ=5.8 ns, Rv=5.3×103 V/W, and D⁎ = 2.07×1010 cmHz/W, respectively.